A NARRATIVE REVIEW OF CORPORATE GOVERNANCE OVERSIGHT AND THE RISE OF GREENWASHING IN ENVIRONMENTAL REPORTING - Munir, Mai Farhana Mior Badrul; Abdullah, Azrul; Noor, Marjan Mohd (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Amid growing global attention to environmental sustainability, companies have intensified environmental reporting as a strategic tool to demonstrate ecological commitment and maintain stakeholder trust. However, the rapid expansion of such reporting has raised growing concerns about its credibility and reliability. Some companies exaggerate or misrepresent their environmental claims, leading to a practice known as greenwashing. This misleading practice undermines the reliability of environmental reporting and erodes stakeholder confidence. Although research on greenwashing has grown substantially, most existing reviews have focused on defining its forms, causes, and effects, with limited exploration of the role of corporate governance in mitigating this practice. In response to this gap, this study aims to review and synthesize the theoretical and empirical insights into the role of corporate governance in mitigating greenwashing within environmental reporting. The findings reveal that while governance mechanisms play a crucial role in mitigating greenwashing, their effectiveness remains context-dependent and empirically inconsistent across governance settings. Current evidence predominantly focuses on board attributes and specialized board committees, such as sustainability and Corporate Social Responsibility (CSR) committees, while other potentially influential board committees, including environmental committees, risk management committees and audit committees, remain underexplored. Moreover, limited studies have examined the interaction between internal and external governance mechanisms in addressing greenwashing. The review further highlights a theoretical imbalance, with agency theory currently dominating research and limited integration of socio-environmental and behavioral perspectives. Conceptually, this study contributes to the literature by underscoring the need for multi-theoretical and behavioral-integrative approaches to explain corporate engagement in greenwashing. Contextually, it extends global sustainability discourse by incorporating emerging markets evidence, particularly Malaysia, where governance effectiveness is shaped by ownership concentration, regulatory transitions and cultural norms. Collectively, this study advances understanding of governance as a key control mechanism, and guides future research on mitigating greenwashing across diverse contexts.